High entropy alloys : innovations, advances, and applications - Srivatsan, T. S.; Gupta, M. (Manoj) (Boca Raton : CRC Press, 2020)
"The book gives a cohesive overview of innovations, advances in processing and characterization, and applications for high entropy alloys (HEAs) in performance-critical and non-performance-critical sectors. It covers manufacturing and processing, advanced characterization and analysis techniques and evaluation of mechanical and physical properties"--
OCLC-licensed vendor bibliographic record.
Keywords: Alloys; Order-disorder in alloys; TECHNOLOGY / Metallurgy